2002
DOI: 10.1037/0882-7974.17.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Models of visuospatial and verbal memory across the adult life span.

Abstract: The authors investigated the distinctiveness and interrelationships among visuospatial and verbal memory processes in short-term, working, and long-term memories in 345 adults. Beginning in the 20s, a continuous, regular decline occurs for processing-intensive tasks (e.g., speed of processing, working memory, and long-term memory), whereas verbal knowledge increases across the life span. There is little differentiation in the cognitive architecture of memory across the life span. Visuospatial and verbal workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

154
1,142
11
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,530 publications
(1,328 citation statements)
references
References 47 publications
154
1,142
11
21
Order By: Relevance
“…Whereas verbal storage-rehearsal processes were correlated strongly with verbal reasoning and very weakly with general ability (see also Cantor et al, 1991;, spatial storage-rehearsal processes predicted both spatial reasoning and general fluid ability strongly. As we noted earlier, these findings are consistent with others demonstrating a close link between "simple" spatial storage and higher order cognitive capabilities such as executive function (Miyake et al, 2001), complex reasoning and Gf (Oberauer, in press;Shah & Miyake, 1996), and free recall of either verbal or visuospatial materials (Park et al, 2002). However, we also found that when our Gf factor was defined in a less spatially biased manner, spatial storage had a substantially weaker correlation with it.…”
Section: The Domain Specificity Of Stm Storage-rehearsal Abilities Ansupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas verbal storage-rehearsal processes were correlated strongly with verbal reasoning and very weakly with general ability (see also Cantor et al, 1991;, spatial storage-rehearsal processes predicted both spatial reasoning and general fluid ability strongly. As we noted earlier, these findings are consistent with others demonstrating a close link between "simple" spatial storage and higher order cognitive capabilities such as executive function (Miyake et al, 2001), complex reasoning and Gf (Oberauer, in press;Shah & Miyake, 1996), and free recall of either verbal or visuospatial materials (Park et al, 2002). However, we also found that when our Gf factor was defined in a less spatially biased manner, spatial storage had a substantially weaker correlation with it.…”
Section: The Domain Specificity Of Stm Storage-rehearsal Abilities Ansupporting
confidence: 92%
“…How should we reconcile these discrepant findings? Park et al (2002) also failed to differentiate the WMC-STM relation across verbal and spatial domains, and therefore ours is not the first failure to replicate. In the Park et al data, the correlation between spatial WMC and STM latent variables was, again, not significantly larger than that between verbal WMC and STM (.84 and .80, respectively).…”
Section: The Relation Between Wmc and Stmmentioning
confidence: 61%
See 1 more Smart Citation
“…1). This confirms existing behavioral evidence suggesting that individual differences in long-term memory correlated with individual differences in working memory (Park et al, 2002(Park et al, , 1996Verhaeghen and Salthouse, 1997). Although verbal fluency tasks are commonly used neuropsychological indicators of frontal lobe dysfunction (Bryan and Luszcz, 2000), which are particularly sensitive Legend: The second column of each correlation indicates the statistical significance (P-value).…”
Section: Discussionsupporting
confidence: 81%
“…However, work on cohorts of human subjects for the third through ninth decades of life indicates that memory loss begins early in adulthood and then continues to worsen in an almost linear fashion, leading to a situation in which the magnitude of decline from 20 to 30 is about as great as that from 70 to 80 years of age (Park et al, 2002). That memory deteriorates during the course of normal aging comes as no surprise to middle-aged people, but that it begins so early and progresses so steadily is perhaps unexpected.…”
Section: Loss Of Synaptic Plasticity In Early Middle Agementioning
confidence: 99%